2021
DOI: 10.1002/ctm2.514
|View full text |Cite
|
Sign up to set email alerts
|

Dual blocking of PI3K and mTOR signaling by DHW‐221, a novel benzimidazole derivative, exerts antitumor activity in human non‐small cell lung cancer

Abstract: Dear Editor, We previously designed and synthesized a novel benzimidazole compound, DHW-221. 1 Here, we evaluated its anti-NSCLC activity as a PI3K/mTOR dual-target inhibitor and comprehensively described for the first time the mechanism underlying the PI3K/AKT/mTOR signaling pathwaymediated antitumor effects of DHW-221. Our findings indicated that the antitumor activity of DHW-221 was significantly stronger than that of NVP-BEZ235, a dual PI3K/mTOR inhibitor currently undergoing a phase II clinical trial.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…Thus, we assessed the effect of DHW-221 on the PI3K/Akt signaling pathway in A549/Taxol and A549 cells by Western blot analysis. Treatment with various concentrations of DHW-221 and GDC-0980 significantly decreased the expression levels of PI3Kp110a and p-Akt in a concentration-dependent manner, while no obvious change was observed in the total Akt level, which suggested that DHW-221 blocked the PI3K/Akt signaling pathway in both A549/Taxol and A549 cells (Figure 5B), agreeing with a previous study (24). FOXO3a, a direct downstream target of Akt, is directly phosphorylated by Akt at the Ser253 site, which allows it to bind to its chaperone protein, 14-3-3, resulting in transfer from the nucleus to the cytoplasm; this process is an important tumorigenic mechanism for evading cancer cell apoptosis (14).…”
Section: Akt-mediated Foxo3a Nuclear Translocation Is Involved In Mit...supporting
confidence: 92%
See 3 more Smart Citations
“…Thus, we assessed the effect of DHW-221 on the PI3K/Akt signaling pathway in A549/Taxol and A549 cells by Western blot analysis. Treatment with various concentrations of DHW-221 and GDC-0980 significantly decreased the expression levels of PI3Kp110a and p-Akt in a concentration-dependent manner, while no obvious change was observed in the total Akt level, which suggested that DHW-221 blocked the PI3K/Akt signaling pathway in both A549/Taxol and A549 cells (Figure 5B), agreeing with a previous study (24). FOXO3a, a direct downstream target of Akt, is directly phosphorylated by Akt at the Ser253 site, which allows it to bind to its chaperone protein, 14-3-3, resulting in transfer from the nucleus to the cytoplasm; this process is an important tumorigenic mechanism for evading cancer cell apoptosis (14).…”
Section: Akt-mediated Foxo3a Nuclear Translocation Is Involved In Mit...supporting
confidence: 92%
“…Previous studies have shown that DHW-221 has a pro-apoptotic effect in NSCLC cells (24). Therefore, we investigated whether DHW-221 triggers apoptosis in A549/Taxol cells.…”
Section: Dhw-221 Triggers Apoptosis and Paraptosis Through The Mitoch...mentioning
confidence: 95%
See 2 more Smart Citations
“…In recent years, 4-amino-quinazoline derivatives, which are kinase inhibitors have attracted attention in the field of pharmaceutical chemistry ( 43 , 44 ). These 4-amino-quinazoline derivatives have also been reported to be inhibitors of PI3Kα and PI3Kδ, suggesting that 4-amino-quinazoline derivatives are potential targeted antitumor drugs ( 6 , 22 , 45 ).…”
Section: Instructionmentioning
confidence: 99%